The contractile vacuole in Ca(2+)-regulation in Dictyostelium: its essential function for cAMP-induced Ca(2+)-influx - Malchow, Dieter (BioMed Central, 2006)
BACKGROUND: cAMP-induced Ca(2+)-influx in Dictyostelium is controlled by at least two non-mitochondrial Ca(2+)-stores: acidic stores and the endoplasmic reticulum (ER). The acidic stores may comprise the contractile vacuole network (CV), the endosomal compartment and acidocalcisomes. Here the role of CV in respect to function as a potential Ca(2+)-store was investigated. RESULTS: Dajumin-GFP labeled contractile vacuoles were purified 7-fold by anti-GFP-antibodies in a magnetic field. The purified CV were shown for the first time to accumulate and release Ca(2+). Release of Ca(2+ )was elicited by arachidonic acid or the calmodulin antagonist W7, the latter due to inhibition of the pump. The characteristics of Ca(2+)-transport and Ca(2+)-release of CV were compared to similarly purified vesicles of the ER labeled by calnexin-GFP. Since the CV proved to be a highly efficient Ca(2+)-compartment we wanted to know whether or not it takes part in cAMP-induced Ca(2+)-influx. We made use of the LvsA(-)-mutant expected to display reduced Ca(2+)-transport due to loss of calmodulin. We found a severe reduction of cAMP-induced Ca(2+)-influx into whole cells. CONCLUSION: The contractile vacuoles in Dictyostelium represent a highly efficient acidic Ca(2+)-store that is required for cAMP-induced Ca(2+)-influx.